Implementation of Zachman Framework in Planning Enterprise Architecture at PT Karya Niaga Abadi (J&T) - Ilma Wulansari Hasdiansa; Andika Isma; Muh. Ibnu Mubin; Ashabul Kahfi; Muhammad Zuhdi (Indonesian Journal of Enterprise Architecture, 2023)
J&T Express Indonesia is present as a shipping service company in the form of documents and packaging / goods. By relying on the IT system in their services, they get a lot of benefits from the service and the quality of the goods/goods. In this research method using the type of research is descriptive research with data collection methods in the form of interviews and interview techniques conducted by researchers to respondents who use J&T Express services to obtain information about enterprise architecture in the J&T Express company. The technique used in collecting data is by conducting interviews with respondents who use J&T Express services and also making observations at the J&T Express company. The next step is to design Enterprise Architecture using the Zachman Framework method. The results showed that the 4 frameworks in the Zachman Framework, namely scope, business model, system model, and technology model can improve the performance and efficiency of the company in planning, implementing, and maintaining information systems used in company operations.